High and low frequency transcutaneous electrical nerve stimulation in post-cesarean pain intensity (Fisioterapia e Pesquisa, 2014)
The current study aim was evaluate the analgesic effect of TENS modulation for high (100 Hz) and low (4 Hz) frequency in post-cesarean pain. 34 postpartum women were randomly divided into three treatment groups: 100 Hz (G100), 4 Hz (G4) and Placebo (GP) (appliance off). Pain intensity was assessed by the NRS (Numeric Rating Scale) before, immediately after application of TENS, and every 20 minutes until an hour after the eletroanalgesia session. We used the Friedman test and Mann-Whitney U test (p